Communication Through Hashtags in Social Movements: A Systematic Literature Review - Kharisma Natalia; Sylvana Virgina Agustya; Irwansyah Irwansyah (Journal La Sociale, 2023)
The hashtag #MeToo was launched by activist Tarana Burke in 2006 to create "empowerment through empathy," expressed on Twitter in response to various allegations of sexual harassment. The use of hashtags in social movements is an approach to initiate connecting actions. This research aimed to examine the development and interconnectedness of communication through hashtags in social movements. The methodology employed was a literature review following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines across sixty selected journals. The findings of this study indicate that hashtags have become a significant means of communication in various social movements, discussing a wide range of topics and fields. The research from 60 selected journals emphasizes the crucial role of hashtags in modern social movements, enabling communication and expression on social media platforms. Hashtags empower support, protests, and discussions on various social issues, exemplified by trends like #MeTooInceste, encouraging survivors to share traumatic experiences. The study recognizes the internet's dual role in criminology, serving as a space for crimes and supportive communities for victims. Notably, the research highlights decentralized information dissemination, centralized data collection, and hashtag activism's global influence. Despite their limitations, social media platforms facilitate critical conversations and social actions. Ultimately, hashtag activism legitimizes social media, underscoring its vital role in contemporary social movements.